The competitive interaction of snails Thiara scabra and Physa doopi on the snail Lymnaea rubiginosa under laboratory conditions - Estuningsih, Sarwitri Endah (Indonesian Animal Sciences Society, 1998)
The competitive interaction of the snails Thiara scabra and Physa doopi against the snail Lymnaea rubiginosa, the intermediate host ofFasciola gigantica has been studied. Aquaria, 60 x 40 x 20 cm and 30 x 20 x 10 cm in size were used, and the two snail species were introduced in different proportion . The results over a one year period showed that the competition between snail L. rubiginosa and T. scabra or P. doopi has started after 8 months as demonstrated by the reduction of the population ofL. rubiginosa and increasing the population of T. scabra or P. doopi. The competitive interaction does not seem to be due to competition for food but to a chemical factors, possibly water-soluble pheromones. The other explanation is discussed . Â Keywords : Snail, intermediate host, Limnaea rubiginosa, Thiara scabra, Physa doopi, Fasciola gigantica, competitive Interaction